2014
DOI: 10.2147/dddt.s68715
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic conditioning improves coronary microcirculation in healthy subjects and patients with heart failure

Abstract: BackgroundRemote ischemic conditioning (RIC) is a treatment modality that suppresses inflammation and improves endothelial function, which are factors involved in the pathogenesis of heart failure (HF) with reduced left ventricular ejection fraction. Coronary flow reserve (CFR) is a physiological index of coronary microcirculation and is noninvasively measured by transthoracic Doppler echocardiography (TTDE). This study aimed to investigate the effects of RIC on CFR in healthy subjects and patients with HF, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…177 In healthy young volunteers, repeated remote ischemic conditioning twice a day for 1 week increased coronary flow reserve, and it did so also in patients with heart failure. 178 In patients undergoing elective percutaneous coronary revascularization, remote ischemic preconditioning did not reduce coronary microvascular resistance in a nontarget vessel. 179 In the Effect of Remote Ischemic Conditioning Before Hospital Admission (CONDI) trial, in patients undergoing primary PCI for acute myocardial infarction, remote ischemic perconditioning with 4 cycles of 5-minute arm ischemia/5-minute reperfusion during transport in the ambulance reduced infarct size but did not improve coronary blood flow.…”
Section: Coronary Vascular Protection By Remote Ischemic Conditioningmentioning
confidence: 98%
“…177 In healthy young volunteers, repeated remote ischemic conditioning twice a day for 1 week increased coronary flow reserve, and it did so also in patients with heart failure. 178 In patients undergoing elective percutaneous coronary revascularization, remote ischemic preconditioning did not reduce coronary microvascular resistance in a nontarget vessel. 179 In the Effect of Remote Ischemic Conditioning Before Hospital Admission (CONDI) trial, in patients undergoing primary PCI for acute myocardial infarction, remote ischemic perconditioning with 4 cycles of 5-minute arm ischemia/5-minute reperfusion during transport in the ambulance reduced infarct size but did not improve coronary blood flow.…”
Section: Coronary Vascular Protection By Remote Ischemic Conditioningmentioning
confidence: 98%
“…These findings were recently supported by another rat study showing a similar beneficial effect even when RIC treatment was not commenced before 4 wk after myocardial infarction (323). In humans, repeated RIC modifies the human inflammatory response and leukocyte adhesion (260) and improves coronary microcirculation in healthy volunteers and patients with heart failure (124,138,147). Currently, two ongoing clinical trials [the Daily REmote Ischemic Conditioning Following Acute Myocardial Infarction (DREAM) study, available at https://clinicaltrials.gov/ct2/ show/NCT01664611, and the Chronic Remote Ischemic Conditioning to Modify Post-MI Remodeling (CRIC-RCT study), available at https://clinicaltrials.gov/ct2/show/NCT01817114] are investigating the effect of prolonged RIC on ventricular function in patients with reduced ventricular function after an acute coronary event.…”
Section: Ric Beyond Acute I/r Injurymentioning
confidence: 73%
“…Indeed, Shimizu and colleagues (45) found that IL-1␤ and IL-10 were unaltered after day 1 but significantly increased after day 10 of RIPC. Furthermore, Kono and colleagues (25) demonstrated that 10 patients with chronic heart failure had decreased TNF␣, IL-6, troponin T, and brain natriuretic peptide after 7 days of RIPC stimulation compared with basal levels. Our results demonstrate acute tefillin did not alter circulating chemokines and leukocyte cell surface receptors (vs. basal levels).…”
Section: Inflammatory Pathwaysmentioning
confidence: 99%